Media Permainan Kahoot dalam Peningkatan Kemampuan Membaca Bahasa Jerman - Genoveva V Nena; Nurming Saleh; Syamsu Rijal (Universitas Negeri Makassar, 2023)
Abstract. The purpose of this research was to determine the students ability to read German texts from class XI SMAN 9 Makassar trough kahoot game as the media. This type of research is classroom action research which consists of two cycles with each cycle consisting of two meetings. The subject of this research was class XI Mia 1 SMA Negeri 9 Makassar. There are two types of research data, namely qualitative data and quantitative data. Qualitative data was obtained from data from teacher and student observations, while quantitative data was obtained from students' German reading test results. The students' German reading test results in the first cycle obtained an average of 74.4 and increased in the second cycle with an average value of 90.4. The results of this study indicate that the use of kahoot game media can improve the students ability to read German teks of class XI Mia SMA Negeri 9 Makassar.Keywords: Reading, Media Kahoot, German